Wit & wisdom of Ratan Tata - Tata, Ratan (New Delhi Hay House Publishers, 2024)
In times of adversity, you have two choices - you can either steal yourself away from the situation or steel yourself up towards it. For Ratan Tata, the choice was made early on. To be given the reins to India's largest business conglomerate can be extremely daunting. But Ratan Tata's takeover as the chairman of the Tata group proved that what is already great can be made even better. His legacy has the innate power to inspire great leadership. His success can motivate any beyond words. But, if how the world sees you is a result of how well you communicate, Ratan Tata's wisdom is unmatchable. This book contains his simplicity, his determination, his defining moments, his generosity, his learning curve, his humility and his intellectual curiosity. From a man who has lived his days redefining success, his experiences and learnings can brighten the light at the end of any entrepreneurial tunnel. If ever, on your journey of life, you need a little nudge, a push or a spark, this book of quotes will never fail to deliver. Not even for a nano second.
Keywords: Biography of Ratan Tata